Macqueripe [sic] Bay, Trinidad, B.W.I. - Packer, J. (Unknown, 2011)
This postcard is a painting of people bathing at Maqueripe Bay.
Colour: Coloured; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Inlets--Trinidad and Tobago; Beaches--Trinidad and Tobago; Bays--Trinidad and Tobago; Beachgoers--Trinidad and Tobago; Bathing beaches--Trinidad and Tobago; Maqueripe Bay